PENGARUH INTEGRASI INTERNAL, INTEGRASI EKSTERNAL, DAN EFEK KOMPLEMENTER INTEGRASI DALAM RANTAI PASOKAN TERHADAP INOVASI PRODUK - Zulaeha Zulaeha; Anjar Priyono (Universitas Mercu Buana, 2017)
ABSTRACT. This research examines the individual and combined effects of internalintegration (II) and external integration (IE) on product innovation (IP), which is basedon ambidexterity theory. This study demonstrated that the combined effect of II and IEare able to facilitate internal exploitation and external exploration to improve productinnovation. Originally, this study used two independent variables only – i.e. II and IE –and product innovation as the dependent variable. Then, two additional independentvariables are added by calculating the combination between II and IE. Using differentcalculation methods, the two variables results in two variables – ie. balanced II and IE(BI) and complementary II and IE (CI) which represents combined effects of II and IE.The object of this study is Small and Medium Enterprises (SMEs) situated inYogyakarata. The results showed that the individual effects of II and IE on IP are notpositively associated with product innovation. Similar with individual effects of II andIE, BI also has no positive impact on product innovation, but CI is able to provide asignificant positive effect on product innovation.